2017
DOI: 10.1158/1078-0432.ccr-16-0919
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in Patients with Hepatocellular Carcinoma—Results of the Observational INSIGHT Study

Abstract: Sorafenib is the only currently approved systemic therapy for advanced hepatocellular carcinoma (HCC). We aimed to evaluate the safety and efficacy of sorafenib therapy in patients with HCC under real-life conditions regarding patient, tumor characteristics, and any adverse events at study entry and at follow-up visits every 2 to 4 months. The current INSIGHT study is a noninterventional, prospective, multicenter, observational study performed in 124 sites across Austria and Germany between 2008 and 2014. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 22 publications
6
49
0
6
Order By: Relevance
“…A recent multicenter study from the United Kingdom also demonstrated Child‐Pugh class, performance status, and albumin‐bilirubin grade as prognostic factors in sorafenib‐treated patients . Other multicenter observational studies have recently demonstrated similar results of Child‐Pugh class as the main determining factor of overall survival . PVT was another frequently reported prognostic factor .…”
Section: Discussionmentioning
confidence: 70%
“…A recent multicenter study from the United Kingdom also demonstrated Child‐Pugh class, performance status, and albumin‐bilirubin grade as prognostic factors in sorafenib‐treated patients . Other multicenter observational studies have recently demonstrated similar results of Child‐Pugh class as the main determining factor of overall survival . PVT was another frequently reported prognostic factor .…”
Section: Discussionmentioning
confidence: 70%
“…Among the chemotherapeutic agents, sorafenib, a small molecule multikinase inhibitor, is considered as a standard treatment for patients with advanced HCC. However, the survival time of patients with advanced HCC is only extended by approximately 2–3 months . Therefore, there is an urgent need to develop novel and promising strategies against advanced HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib was the first systemic treatment approved in HCC, and its effectiveness and safety were externally validated in prospective randomized studies and in cohort studies . This manuscript reviews the available data regarding systemic treatment after LT in this special population.…”
Section: Summary Of Studies With Patients Treated With Sorafenib Aftementioning
confidence: 99%